2022
DOI: 10.1111/bjet.13205
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of instructors' and students' perspectives on remote delivery of courses during the COVID‐19 pandemic

Abstract: The world-wide pivot to remote learning due to the exogenous shocks of COVID-19 across educational institutions has presented unique challenges and opportunities. This study documents the lived experiences of instructors and students and recommends emerging pathways for teaching and learning strategies post-pandemic. Seventy-one instructors and 122 students completed online surveys containing closed and open-ended questions. Quantitative and qualitative analyses were conducted, including frequencies, chi-squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 21 publications
1
30
0
1
Order By: Relevance
“…During the pandemic, adjusting to the increase in online learning seems to have been just as challenging for academic staff as for students, as staff often needed to overcome their digital skills gap and reconfigure their pedagogical approaches for online learning environments. Chen et al ( 2022 ) report the perceived views and attitudes of both staff and students in a Canadian university towards ERT. Whilst both groups were being resilient and adapted quickly to the disruption, the researchers indicate that the long‐term effectiveness of online learning and teaching needs to be evaluated in a continuous manner.…”
Section: Higher Education In the Westmentioning
confidence: 99%
“…During the pandemic, adjusting to the increase in online learning seems to have been just as challenging for academic staff as for students, as staff often needed to overcome their digital skills gap and reconfigure their pedagogical approaches for online learning environments. Chen et al ( 2022 ) report the perceived views and attitudes of both staff and students in a Canadian university towards ERT. Whilst both groups were being resilient and adapted quickly to the disruption, the researchers indicate that the long‐term effectiveness of online learning and teaching needs to be evaluated in a continuous manner.…”
Section: Higher Education In the Westmentioning
confidence: 99%
“…In this regard, Gleason and Greenhow (2017) argued that hybrid teaching fosters students' participation in the classroom, their feelings of belonging and confidence, and their ability to contribute ideas, and Potra et al (2021) suggested that the hybrid approach has become a bridge between online and face-to-face teaching after the onset of the COVID-19 pandemic. Additionally, Chen et al (2022) evidenced that, in the context of adaptation towards online courses by COVID-19, instructors and students do not want face-to-face learning to disappear, rather, they recommend combining learning opportunities through face-to-face and online courses according to personal preferences.…”
Section: Conclusion Implications and Future Researchmentioning
confidence: 99%
“…Communication in an online classroom is restricted by digital tools available in the meeting software that the school relies on such as chatbox, raise-hand functions, webcam and audio, etc. (Chen et al, 2022); effective communication therefore becomes bundled with computer literacy of both teachers and students. This form of digitalised communication has henceforth brought upon another level of communication barrier and even distance that teachers need to overcome in achieving the same level of trust and/or closeness with their students in a traditional classroom.…”
Section: Emotional Capitalmentioning
confidence: 99%